2019
DOI: 10.1001/jamaoncol.2018.2956
|View full text |Cite|
|
Sign up to set email alerts
|

Association of Breast and Ovarian Cancers With Predisposition Genes Identified by Large-Scale Sequencing

Abstract: The results of this large-scale exome sequencing of patients and controls shed light on both well-established and controversial non-BRCA predisposition gene associations with breast or ovarian cancer reported to date and may implicate additional breast or ovarian cancer susceptibility gene candidates involved in DNA repair and genomic maintenance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
148
4
8

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(172 citation statements)
references
References 48 publications
12
148
4
8
Order By: Relevance
“…Four different truncating ATM mutations were seen in six cases (1% of non‐ BRCA cases). There is evidence that ATM protein‐truncating mutations are associated with a twofold to threefold increase in breast cancer risk . A meta‐analysis of 26 studies (including 4,076 cases and 2,389 controls) performed in 2009 reported an OR of 2.1 (95% CI 1.03–4.21) for breast cancer for carriers of truncating ATM mutations .…”
Section: Discussionmentioning
confidence: 99%
“…Four different truncating ATM mutations were seen in six cases (1% of non‐ BRCA cases). There is evidence that ATM protein‐truncating mutations are associated with a twofold to threefold increase in breast cancer risk . A meta‐analysis of 26 studies (including 4,076 cases and 2,389 controls) performed in 2009 reported an OR of 2.1 (95% CI 1.03–4.21) for breast cancer for carriers of truncating ATM mutations .…”
Section: Discussionmentioning
confidence: 99%
“…91 Variants have been associated with ovarian cancer risk (OR = 18.50, 95% CI 2.56-808.1). 92 However, numerous studies have not found germline TP53 variants to be significantly associated with ovarian cancer or to affect risk. 61,93-96…”
Section: Tp53mentioning
confidence: 99%
“…The crucial role of TP53 is exemplified by Li‐Fraumeni syndrome, a disorder with close to 100% cancer incidence by age 70; the median age of ovarian cancer in these patients is 39.5 years . Variants have been associated with ovarian cancer risk (OR = 18.50, 95% CI 2.56‐808.1) . However, numerous studies have not found germline TP53 variants to be significantly associated with ovarian cancer or to affect risk …”
Section: Introductionmentioning
confidence: 99%
“…5,7,11 The missing heritability could be partially attributed to risk-associated rare coding variants (MAF < 0.5%), which typically have large effect sizes, as demonstrated in multiple hereditary breast cancer genes, such as BRCA1, BRCA2, ATM, TP53, CHEK2, PALB2, CDH1, STK11, NF1 and PTEN. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] Two recent case-control association studies conducted in European-ancestry populations discovered many new pathogenic coding variants by sequencing known cancer predisposition genes. 22,23 However, rare coding variants in known breast cancer susceptibility genes and other less well-characterized genes have not been adequately investigated in Asian populations.…”
Section: Introductionmentioning
confidence: 99%